Natural infection of triatomines with trypomastigote of trypanosoma cruzi in the province of Nazca, department of Ica - Uyema T., Norma (2022)
Chagas diseases is a zoonosis caused by Tripanosoma cruzi. In Perú the main vector is Triatoma infestans, triatomineo known as "chirimacha". We determined the Domiciliary infestation by visiting 169 family houses and we found 26 (12.26%) infested with chirimacha. During August 17 -25, 1996, we collected 228 triatomineos, 211 (92.46%) were examined and 29 (13.74%) were infected with Tcruzi. In one house (0.26%) of 26 infested houses we found that chirimachas examined were infected with T-cruzi, since ninpha II stage until adult parasite in 29 (13.74%) examined, being the bedroom where we found the greatest number of infected triatomineos.